Effectiveness of Chlorhexidine Digluconate Mouth Rinse in Improving Oral Health in Orthodontic Patients with Fixed Appliances - Ghada Dh Al-Sayagh; Ruba J Mohammed; Wafaa Gh Al-Shahery (University of Mosul, College of Dentistry, 2013)
Aims: To evaluate the effect of chlorhexidine digluconate rinsing solution on plaque and gingival bleeding in orthodontic patients with fixed appliances. Materials and Methods: This study included 42 orthodontic patients (29 females and 13 males), who were undergoing treatment in orthodontic postgraduate clinic of the collage of Dentistry, Mosul University. The patients of this study had a mean age of 18 years (range 12-28 years). The patients were divided in to control group (brushing only, N=20) and an experimental group (brushing +chlorhexidine digluconate mouth rinse, N=22). Plaque, gingival indices scores, in addition to pocket depth were measured in different three time periods (day 0, two weeks and four weeks). Results: Plaque, gingival indices scores, in addition to pocket depth shows statically significant differences at level (p≤0.05) among different genders between the two groups for each of the three time periods. Conclusions: The use of chlorhexidine digluconate based mouth rinses reduced bacterial plaque accumulation, pocket depth and improved the gingival index